Authorship and creation for university students - Graziele Aline Zonta; Andréa Vieira Zanella (Ciencias Psicológicas, 2021)
The aim of this study was to investigate the meanings of creation and the possibilities of authorship for students from two public universities. Reading and writing workshops with students, which were recorded via audio recordings and fieldnotes constituted the field of study. The analyses were based on the theoretical perspectives of Bakhtin and Vygotski and focused, from the students’ point of view, on the social places institutionally occupied by professors and students and the meanings about the academic practices and their consequences for the possibilities of authorship and creation. The results indicate places of inequality in the relationship between peers from public and private education, the individual responsibilization of the students for their trajectories within the university and the signification of academic authorship as responsive to the productivist logic guided by the commodification of scientific production.